The effect of hip-hop on the social movement - Fadil, Thami F. (Eximia, 2022)
According to two divergent theories, the new social movement theory, and the political opportunity theory, this study examines how hip-hop music, with its grim depictions of urban reality and youth manifestos, can be both the mirror and the engine of a social movement Upon closer inspection of the work of two notable hip-hop performers, it becomes clear that both musicians are striving to "represent," influence, and carry the mantle of movement leaders in their portrayal of women in rap. Hip-hop music, which has spread from the Bronx to Los Angeles and spurred record sales and fashion trends for young people everywhere in between, has sparked a great deal of scholarly curiosity. Hip-hop was condemned as a detrimental influence on youngsters by parents and politicians practically as soon as it was created as a genre. Despite the dismissive attitude of the doubters, millions of people transformed the country's heroes into cultural icons by following in the footsteps of their idols. Increasing evidence suggests that hip-hop was a social movement fueled by the wrath of historically marginalized youth, primarily of African American heritage, according to a growing corpus of studies. Hip significance, hops, on the other hand, has not yet been fully realized. Throughout history, societal groups have used music to disguise threats: spirituals sparked African American demonstrations from enslavement to the civil rights movement, and witty folk tunes masked significant antiwar feelings during many conflicts, among other things. As per the conclusion of this work, the lust for power and wealth and the use of drugs and alcohol are all common themes in hip-hop. Even though many iconic hip-hop albums deal with these topics, their relevance cannot be overstated, even though they are generally perceived as damaging to society. This kind of music will go on with these topics for the foreseeable future as long as they are relevant. On the other hand, several rappers focus on socially conscious topics, such as issues in their communities that need to be addressed via reform or change. This group of artists typically deals with political and social themes in their work. Considering hip-enduring hop's popularity, protest music is likely to continue in this vein while the social movement has developed traction and achieved its objectives even after joining forces with other organizations.